2014
DOI: 10.1093/carcin/bgu198
|View full text |Cite
|
Sign up to set email alerts
|

ETV5 transcription program links BDNF and promotion of EMT at invasive front of endometrial carcinomas

Abstract: Myometrial infiltration represents a main clinical determinant of endometrial carcinomas (EC) presenting as aggressive high-grade deeply invasive neoplasms, substantially associated with risk of recurrence and death. The up-regulation of ETV5 transcription factor linked to the promotion of epithelial to mesenchymal transition is considered as a basic mechanism underlying the initial steps of EC invasion. In this work, we aimed to investigate the transcription program of tumor invasion regulated by ETV5. We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…Interestingly, BDNF demonstrated a principal role coordinating ETV5 mediated EMT in EC. Impairment of BDNF/TrkB/ERK axis in EC cells reversed the aggressive and invasive phenotype promoted by the upregulation of ETV5 at the invasive front (Alonso-Alconada et al 2014). ETV5 related proteomic approach performed in Hec1A cell line reinforced a role of this transcription factor in regulation of the migratory and invasive tumor behavior (Monge et al 2009).…”
Section: Cell Signaling Pathwaysmentioning
confidence: 93%
“…Interestingly, BDNF demonstrated a principal role coordinating ETV5 mediated EMT in EC. Impairment of BDNF/TrkB/ERK axis in EC cells reversed the aggressive and invasive phenotype promoted by the upregulation of ETV5 at the invasive front (Alonso-Alconada et al 2014). ETV5 related proteomic approach performed in Hec1A cell line reinforced a role of this transcription factor in regulation of the migratory and invasive tumor behavior (Monge et al 2009).…”
Section: Cell Signaling Pathwaysmentioning
confidence: 93%
“…CT26 LifeAct-GFP and HCT116-Luc cells were generated by lentiviral infection as described previously (14). HCT116-Luc cells were selected using blasticidine HCl (10 mg/mL).…”
Section: Generation Of Stable Cell Linesmentioning
confidence: 99%
“…What is of considerable interest is that the BDNF/TrkB pathway has been shown to mediate the resistance to anoikis of multiple cancers (9,18,(25)(26)(27)(28)(29). it was shown that in multiple cancers, metastatic tumor cells have up-regulated TrkB and BDNF compared to tumor cells that did not metastasize (18,26,29).…”
Section: Role In Epithelial To Mesenchymal Transition and Anoikismentioning
confidence: 99%